ANALYSIS CONTENT OF TRACEELEMENTS IN TABULAR WATERS KRASNOKUTSK FIELD (Academic journal Industrial Machine Building Civil Engineering, 2017)
Analyzed the content of trace elements iodine, bromine tabular waters Krasnokutsk field. Deposits studied field with a high content of iodine and bromine ions. The relation between high iodine content in groundwater and oilfield related thermobaric conditions. Keywords: trace element, iodine, bromine, tabular water, oil pools, thermobaric conditions.